Pengaruh Strategi Lightening The Learning Climate terhadap Kemampuan Menulis Teks Deskripsi Bahasa Indonesia Siswa-Siswi Kelas VII SMP Gajah Mada Medan Tahun Pembelajaran 2022/2023 - Windi Asria Lumbangaol; Harlen Simanjuntak; Beslina Afriani Siagian; Imelda Butar Butar (Departement of Mathematics Education, 2023)
This study aims to determine the effect of the Lightening the Learning Climate strategy on the ability to write Indonesian language description texts for Grade VII students of Gajah Mada Middle School, Medan, in the 2022/2023 Academic Year. This type of research is a Quantitative Experimental Research with a One-group Pretest and Posttest research design. The population in this study were all students of class VII with a total of 32 students determined by the Saturated Sampling Technique. The data analysis technique used is the Normality test, Homogeneity test and Hypothesis Test. After conducting research for the pretest and posttest experiments using the Lightening the Learning Climate strategy, the average value of the pretest was 52.73 and that of the Posttest class was 77.73. Pretest and posttest data prerequisite test results stated that the sample was normally distributed and homogeneous. From the results of testing the hypothesis in this study, the